Retracing the history of literary translation in Poland : people, politics, poetics - Heydel, Magda; Ziemann, Zofia (2022)
"This book brings a fresh perspective on the Polish literary translation landscape, offering unique insights into the social, political, and ideological underpinnings of Polish translation history for an English language audience for the first time. Employing a problem-based approach, the book creates a map of different research directions in the history of literary translation in Poland, corresponding to the book's six thematic sections, toward offering a holistic, rather than chronological, perspective on the discipline's development in the region. The six sections - translators' lives, translation modes, translation poetics, translation politics, translation systems, and digital humanities approaches to studying translation history - explore topics of particular interest in translation research more broadly today, including translation and migration, the agency of women translators, indirect translation, and translators as cultural agents. The twenty contributions taken together demonstrate the ways in which Polish culture has represented translated work in its own way, informed and shaped by socio-political changes in Polish history, thereby situating research on Polish translation within the growing body of work on Central and Eastern European literary translation research traditions. This collection offers a window into key themes from Poland's literary translation history and a counterpoint to existing research on Western literary canons for students and scholars in translation studies, comparative literature, cultural studies, and Slavonic studies